Antecedents and Consequences of Infidelity in Cross-border Business Relationships - Leonidou, Leonidas C.; Aykol, Bilge; Fotiadis, Thomas A.; Christodoulides, Paul (My University, 2017)
The volatile, complex, and distant nature of the international business environment inevitably gives rise to incidences of infidelity among interacting exporters and importers. The authors propose and test a theoretically anchored model of the antecedents and consequences of infidelity in exporter-importer (E-I) working relationships. The findings confirm that importer’s infidelity incidences are higher in those cases where trust, satisfaction, commitment, and cooperation are low in the relationship. In fact, the association between poor relationship quality and infidelity becomes stronger when the relationship is at a declining stage and is relatively young. The existence of infidelity in the relationship will lead to either punitive actions or reassessment measures on the part of the exporter, which are moderated by the degree of long-term orientation and social bonding that exists between the interacting parties.
Keywords: Infidelity; Relationship quality; Exporting; Exporter-importer relationships